MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI MELALUI MEDIA E-LKS WAYANG SUKURAGA PADA SISWA KELAS III DI SEKOLAH DASAR - Halimah; Dyah Lyesmaya; Arsyi Rizqia Amalia; Ira komala; Mastoah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article covers the discussion about the improvement of students' writing descriptive skills through the Sukuraga puppet as electronic student worksheets media. The method applied was CAR (Classroom Action Research) to improve learning problems in the classroom, especially the description writing skills. The population in the study was carried out for students of class III in SDN Mekarjaya in the academic year 2021/2022, which consisted of 8 students, 4 male and female students. The results of the data indicated that the application of electronic media student worksheets of Sukuraga puppet was able to improve students' descriptive writing skills. It could be seen from the result of the final students’ descriptive writing skill test that the students experienced a significant improvement starting from the pre-cycle, cycle I, and cycle II that have been discussed. Based on preliminary research data, the student’s average score on the descriptive writing test was 63, which was still lower than the minimum completeness criteria (KKM) score determined at school. Nevertheless, after applying the electronic student worksheets media of Sukuraga puppet in cycle I, the score of the descriptive writing test was 71 then in cycle II, the score was 80. It could be concluded that the use of E-Students Worksheet media could further develop the descriptive writing skills of the third-grade students of elementary school III Mekarjaya.